(untitled) (Research, Society and Development, 2021)
Cancer is a major public health problem and among the treatments available, chemotherapy is one of the most used, although chemotherapy drugs are toxic for cancer cells, they have low specificity and, consequently, become toxic for healthy cells as well. A strategy that seeks to increase the therapeutic effectiveness of chemotherapy and minimize adverse effects is the use of nanoparticles. For this purpose, the objective was to generally review the available literature on the anticancer activity of nanoparticles loaded with bromelain in the pharmaceutical field. This is a systematic review that had the question “What is the anticancer activity of nanoparticles loaded with bromelain in the field of pharmaceutical nanotechnology?”. Eight articles were included in this review, all of which presented a quantitative data approach, in which 50% of the publications were concentrated in the year 2014 and 2016, all available in English; and India was the country with the highest number of publications (50%). This study allowed us to observe that nanoparticles loaded with bromelain have the potential to act in the treatment of cancer patients, having an antiproliferative and antitumor effect. It is considered that further research should be carried out in this line of investigation, in order to prove the need to find new treatments for cancer and the action potential of bromelain.